The role of extracellular traps in ischemia reperfusion injury - Zhang, Feilong; Li, Yuqing; Wu, Jiyue; Zhang, Jiandong; Cao, Peng; Sun, Zejia; Wang, Wei (Frontiers in Immunology, 2022)
In response to strong signals, several types of immune cells release extracellular traps (ETs), which are web-like structures consisting of DNA decorated with various protein substances. This process is most commonly observed in neutrophils. Over the past two decades, ET formation has been recognized as a unique mechanism of host defense and pathogen destruction. However, the role of ETs in sterile inflammation has only been studied extensively in recent years. Ischemia reperfusion injury (IRI) is a type of sterile inflammatory injury. Several studies have reported that ETs have an important role in IRI in various organs. In this review, we describe the release of ETs by various types of immune cells and focus on the mechanism underlying the formation of neutrophil ETs (NETs). In addition, we summarize the role of ETs in IRI in different organs and their effects on tumors. Finally, we discuss the value of ETs as a potential therapeutic target for organ IRI and present possible challenges in conducting studies on IRI-related ETs as well as future research directions and prospects.